Effects of Eccentric Training of Wrist Extensors Versus Digital Latching & Lateral Rotation of Forearm in Lateral Epicondylitis – A Randomized Controlled Trial (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
AbstractBackground: Lateral Epicondylitis (LE) is a degenerative tendon condition marked by pain due to repetitive wrist extension and gripping. It is now understood to involve tendon degeneration rather than inflammation. Eccentric training improves tendon healing, while newer approaches like Digital latching & lateral rotation of forearm (DLaLR) target both muscle imbalance and joint mechanics. This combined strategy may offer more effective relief and functional recovery.OBJECTIVES: To compare the effects of therapeutic ultrasound and wrist extensors eccentric training versus therapeutic ultrasound and DLaLR in LE.METHODS: In a randomized controlled trial, 42 participants were equally divided into two groups using concealed envelope method. Group A (n=21) received therapeutic ultrasound with eccentric wrist extensor training, while Group B (n=21) received therapeutic ultrasound with DLaLR. Visual Analogue Scale (VAS), Patient Rated Tennis Elbow Evaluation (PRTEE), and pain-free grip strength (PFGS) were assessed at 0th day and after 4th weeks.RESULTS: There were no significant difference on VAS, PRTEE and PFGS on 0th day between the groups. Both treatment methods were found to be significantly effective for VAS, PRTEE and PFGS on 4th week. Group B showed more significant improvement (p
Keywords: Lateral Epicondylitis, Digital latching & lateral rotation of forearm, Patient Rated Tennis Elbow Evaluation, pain-free grip strength.